Modified tubularized incised plate urethroplasty in distal hypospadias repair: Stepwise technique with validated functional and cosmetic outcome. Issue 1 (February 2017) - Spinoit, A.-F.; Radford, A.; Ashraf, J.; Gopal, M.; Subramaniam, R.
Summary: Objective: To describe modification of the tubularized incised plate urethroplasty (TIP) for distal hypospadias, and assess its efficacy, and functional and cosmetic outcomes. Methods: A prospective evaluation of a consecutive series of patients operated for primary distal hypospadias was conducted at a tertiary reference center. A standardized modification of the TIP (mTIP) procedure was performed on a 10 French catheter. Clinical data were collected in a dedicated database. Intraoperative variables, postoperative complications and outcomes, by means of uroflowmetries and a validated (HOPE) questionnaire, were assessed. Efficacy was evaluated with the reported complications: functional outcome was evaluated with uroflowmetries and cosmetic assessment by a validated questionnaire (HOPE). A descriptive statistical analysis was performed. Results: Of the 112 boys operated between 30/09/2011 and 1/04/2014, 50 completed long-term follow-up with functional and esthetic evaluation, as required for inclusion. Median age at surgery was 25 months (range 14–156); median follow-up time was 21.5 months (range 6–48). Complications requiring re-intervention occurred in 2/50 boys. Uroflowmetry presented a bell-shaped curve in 47/50 boys, and the median HOPE score was 9.5 (range 7.6–10.0). Conclusion: The mTIP procedure provided satisfactory long-term functional and cosmetic outcomes, as validated by uroflowmetries and standardized questionnaire.